2020
DOI: 10.1186/s12967-019-02185-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic serum biomarkers for prognosis of disease progression in prostate cancer

Abstract: Background Predicting the clinical course of prostate cancer is challenging due to the wide biological spectrum of the disease. The objective of our study was to identify prostate cancer prognostic markers in patients ‘sera using a multi-omics discovery platform. Methods Pre-surgical serum samples collected from a longitudinal, racially diverse, prostate cancer patient cohort (N = 382) were examined. Linear Regression and Bayesian computational app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 41 publications
(46 reference statements)
0
44
0
Order By: Relevance
“…TNC re-expression may also take place during PCa bone metastasis, since it has been shown that bone metastatic PCa cells interact with TNC through α9β1 integrin when cultured in osteomimetic surfaces containing this glycoprotein [170]. In addition, in a multi-omics approach study, TNC protein was detected in the circulation prior to radical prostatectomy and its combination with three other serum markers and metabolites could predict BCR-free survival with high accuracy [171]. Re-expression of TNC in the bone could be a factor attracting disseminated PCa cells in this site, supporting the idea that cancer cells tend to metastasize in microenvironments similar to the primary tumor.…”
Section: Role Of Cafs In Pca Bone Metastasismentioning
confidence: 99%
“…TNC re-expression may also take place during PCa bone metastasis, since it has been shown that bone metastatic PCa cells interact with TNC through α9β1 integrin when cultured in osteomimetic surfaces containing this glycoprotein [170]. In addition, in a multi-omics approach study, TNC protein was detected in the circulation prior to radical prostatectomy and its combination with three other serum markers and metabolites could predict BCR-free survival with high accuracy [171]. Re-expression of TNC in the bone could be a factor attracting disseminated PCa cells in this site, supporting the idea that cancer cells tend to metastasize in microenvironments similar to the primary tumor.…”
Section: Role Of Cafs In Pca Bone Metastasismentioning
confidence: 99%
“…Genomic amplification in TNC gene associates with highly aggressive neuroendocrine PCa occurrence [37]. In a multi-omics approach study, TNC protein was one of the panel of four markers detected in preoperative serum samples and collectively predict biochemical relapse events with high accuracy [38].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblastic bone metastasis stromal seven-gene signature was induced in the mouse- may suggest that it would be relevant to examine TNC mRNA and protein expression in human bone metastasis or ideally matched primary-metastasis cases in order to understand the kinetic of TNC in terms of disease progression. Given that TNC expression was found elevated from 0% in BPH stroma to 47% in tumor-associated stroma [24], its detection in circulation [38], its immunomodulatory role [40], indicates TNC as a promising drug target and disease determining factor. TNC clinical progression predictive value is performing best in earlier stage, low risk PCa, while our data show that in high risk PCa low number of TNC producing cells were associated with poor prognosis possibly due to changes in tissue remodeling and thus variable TNC levels.…”
Section: Discussionmentioning
confidence: 99%
“…Technological advancements have enabled novel strategies to discover individual biomarkers as well as panels of markers derived from different -omics platforms [5][6][7][8][9][10][11][12][13][14]. These technologies harvest substantial volumes of data at multiple biological levels and sift the resulting large data sets with informatics tools including artificial intelligence (AI).…”
Section: Introductionmentioning
confidence: 99%